Proceedings of the Interaction Design and Children Conference 2020
DOI: 10.1145/3392063.3394408
|View full text |Cite
|
Sign up to set email alerts
|

Investigating children's spontaneous gestures when programming using TUIs and GUIs

Abstract: Spontaneous gestures produced during mathematics learning have been widely studied, however, research on the role of gesture in computing education is limited. This paper presents an investigation into children's use of spontaneous gestures when learning programming using either a tangible user interface (TUI) or a graphical user interface (GUI). The study explored the relationship between spontaneous gestures, interface type and learning outcomes in a programming lesson for primary school students aged 6-7. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…One of the studies [107] that saw a difference between how children embodied technologies looked at the difference in the embodiment patterns of the children themselves rather than the technologies. They found that children who were considered as "high gesturers" during the reflective process had a higher understanding of abstract concepts compared to "low gesturers".…”
Section: Embodied Versus Dis-embodied Learning Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the studies [107] that saw a difference between how children embodied technologies looked at the difference in the embodiment patterns of the children themselves rather than the technologies. They found that children who were considered as "high gesturers" during the reflective process had a higher understanding of abstract concepts compared to "low gesturers".…”
Section: Embodied Versus Dis-embodied Learning Methodsmentioning
confidence: 99%
“…or programming [107,104,102], with few studies exploring the arts, such as music, independent of STEM knowledge -Andantino [88] being an excellent example of that. We find that other studies involving design and other arts only used it as a teaching method for a more STEM-related goal rather than as the sole purpose of engagement.…”
Section: Subjects Focused On In Embodied Learning Studiesmentioning
confidence: 99%
“…The role of gestures in education has been widely researched in areas such as mathematics (Alibali & Nathan, 2012;Núñez, 2008), science (Roth & Lawless, 2002;Solvang & Haglund, 2021;Tang et al, 2022), and programming (Almjally et al, 2020;Almjally et al, 2023;Solomon et al, 2018), as well in design and metaphor studies (Arvola & Artman, 2007;Cuccio & Fontana, 2017;Iriskhanova & Cienki, 2018;Mittelberg, 2018;Mittelberg & Waugh, 2009;Müller & Tag, 2010). Nevertheless, the application of MIG-G remains sparse.…”
mentioning
confidence: 99%